Synthesis, Characterization and Antimicrobial Activity of Metal Chelates of 5-(4-N,N-Diphenylamino sulfonyl phenyl azo)-8-hydroxy Quinoline - Patel, A.U. (Asian Journal of Chemistry, 2010)
4-N,N-Diphenylamino sulfonyl phenyl amine was synthesized, diazotized and coupled with 8-hydroxyquinoline. The resultant 5-(4-N,N-diphenylamino sulfonyl phenylazo)-8-hydroxy quinoline (PSQ) was characterized by elemental analysis and spectral studies. The transition metal chelates viz. Cu2+, Ni2+, Co2+, Mn2+ and Zn2+ of PSQ were prepared and characterized by metal-ligand (m:L) ratio. IR and reflectance spectro-scopy and magnetic properties. The antifungal activity of PSQ and its metal chelates was screened against various fungi. The results show that all these samples are good antifungal agents.